Oral disorders in patients with chronic renal failure. Narrative review - Carolina Hernández (Universidad de Concepción., 2016)
Chronic renal failure (CRF) is one of the best known renal diseases. It is characterized by a deterioration in the overall renal function and is associated with other conditions such as hypertension, diabetes mellitus, uropathy, chronic glomerulonephritis and autoimmune diseases. Patients with CRF show alterations of the masticatory system that are specific to the disease and other type of disorders as a result of treatment. Oral health in dialysis and transplant patients tends to be poor, which makes them more likely to develop pathological conditions in the oral cavity, potentially increasing morbidity, mortality and affecting the quality of life of patients. Among the lesions we can find dysgeusia, periodontitis, candidiasis, gingival bleeding, petechiae, and joint alterations. Gingivitis and xerostomia associated to long-term use medications can cause oral lesions. Children with CRF show two oral conditions of interest: high incidence of dental anomalies and low caries activity. In patients receiving a kidney transplant, previous dental treatment is critical because the immune status of the patient will be affected not only by the toxemia, but by the immunosuppressive drugs used to prevent transplant rejection. Therefore, the dentist plays an important role in training parents and/or guardians, doctors and paramedics on the treatment of oral lesions in these patients